Application of a novel finger temperature device in the assessment of subjects with Raynaud's phenomenon - Aleksiev, Teodor; Ivanova, Zlatina; Dobrev, Hristo; Atanasov, Nikolay (Skin research and technology, 2021)
Introduction Finger skin thermometry is one of the most commonly used methods for evaluating the response of the digital vessels to cold stimulation. The aim of this study was to evaluate the applicability of a novel finger skin temperature device for performing cold‐stimulation test (CST) in subjects with primary and secondary Raynaud's phenomenon (RP). Methodology A total of 155 consecutive subjects were studied. They were divided into three groups: 73 patients with primary RP (8 males, 65 females, mean age 38.5 ± 16.2), 42 patients with secondary RP (4 males, 38 females, mean age 49.6 ± 13.1, connected with lupus erythematosus and systemic scleroderma), and 40 healthy controls (5 males, 35 females, mean age 38.8 ± 16.6). Standardized CST consisting of exposure of both hands to water with a temperature of 10℃ for 5 minutes was performed. Changes in skin temperature of both wrists and 2‐5 fingers were measured using a novel finger temperature device (Courage & Khazaka). Measurements were made before and 5, 10, 15, 20, 25, and 30 minutes after cold stimulation. The time of recovery for baseline temperature of all fingers below 15 minutes was considered normal. Results The CST was normal in 6 (8.2%) of the patients with primary RP, in 7 (16.6%) of the patients with secondary RP, and in 28 (70%) of the healthy control subjects. The time of complete recovery of baseline temperature with respect to the first finger and for all 2‐5 fingers in the three groups was as follows: 24.8 and 28.5 minutes (primary RP), 21.7 and 26.8 minutes (secondary RP), and 11.1 and 15.2 minutes (healthy subjects). Furthermore, the microcirculation was seriously disturbed (rewarming time >31 minutes of all 2‐5 digits of both hands) in 54.1% (n = 79), 34.5% (n = 29) and 5% (n = 4) in the same study groups. Discussion Our results suggested that skin microcirculation is more disturbed in patients with primary RP than in patients with secondary RP. In support of this unexpected finding were the results reported by Ruaro B. et al (2019). They investigated the blood perfusion (BP) by laser speckle contrast analysis (LASCA) at different skin areas of hands and found that it was significantly lower in primary RP than in secondary RP related to systemic sclerosis. Conclusion The new finger temperature device used could be considered useful for performing cold‐stimulation test in patients with Raynaud's phenomenon.